Static strength calculation of DN 350 branch pipe cutting-in in the main circulation pipeline of reactor plant WWER-1000. (February 2019) - Ovsenev, A E; Pimenov, N; Semenov, A O; Bibik, I S; Balachkov, M M
Abstract: Nowadays the total electricity generated in nuclear power plants in Russian Federation is approximately 18% of all power generation. There are 36 reactors in operation in Russia, 19 of which are reactor plants WWER-1000. A planned operation lifetime of these plants is 30 years and most of them have served for this period. To extend reactor working lifetime it is necessary to carry out the calculation for possibility justification of continued operation of reactor equipment and pipelines. The paper presents the static strength calculation of DN 350 branch pipe cutting-in in the main circulation pipeline of reactor plant WWER-1000. According to calculation results a following conclusion is made: if the static strength of DN 350 branch pipe cutting-in meets the requirements of technical standard, the continued operation of this pipeline section will be possible.